(x-3)(7x+16)=153

Simple and best practice solution for (x-3)(7x+16)=153 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)(7x+16)=153 equation:


Simplifying
(x + -3)(7x + 16) = 153

Reorder the terms:
(-3 + x)(7x + 16) = 153

Reorder the terms:
(-3 + x)(16 + 7x) = 153

Multiply (-3 + x) * (16 + 7x)
(-3(16 + 7x) + x(16 + 7x)) = 153
((16 * -3 + 7x * -3) + x(16 + 7x)) = 153
((-48 + -21x) + x(16 + 7x)) = 153
(-48 + -21x + (16 * x + 7x * x)) = 153
(-48 + -21x + (16x + 7x2)) = 153

Combine like terms: -21x + 16x = -5x
(-48 + -5x + 7x2) = 153

Solving
-48 + -5x + 7x2 = 153

Solving for variable 'x'.

Reorder the terms:
-48 + -153 + -5x + 7x2 = 153 + -153

Combine like terms: -48 + -153 = -201
-201 + -5x + 7x2 = 153 + -153

Combine like terms: 153 + -153 = 0
-201 + -5x + 7x2 = 0

Begin completing the square.  Divide all terms by
7 the coefficient of the squared term: 

Divide each side by '7'.
-28.71428571 + -0.7142857143x + x2 = 0

Move the constant term to the right:

Add '28.71428571' to each side of the equation.
-28.71428571 + -0.7142857143x + 28.71428571 + x2 = 0 + 28.71428571

Reorder the terms:
-28.71428571 + 28.71428571 + -0.7142857143x + x2 = 0 + 28.71428571

Combine like terms: -28.71428571 + 28.71428571 = 0.00000000
0.00000000 + -0.7142857143x + x2 = 0 + 28.71428571
-0.7142857143x + x2 = 0 + 28.71428571

Combine like terms: 0 + 28.71428571 = 28.71428571
-0.7142857143x + x2 = 28.71428571

The x term is -0.7142857143x.  Take half its coefficient (-0.3571428572).
Square it (0.1275510204) and add it to both sides.

Add '0.1275510204' to each side of the equation.
-0.7142857143x + 0.1275510204 + x2 = 28.71428571 + 0.1275510204

Reorder the terms:
0.1275510204 + -0.7142857143x + x2 = 28.71428571 + 0.1275510204

Combine like terms: 28.71428571 + 0.1275510204 = 28.8418367304
0.1275510204 + -0.7142857143x + x2 = 28.8418367304

Factor a perfect square on the left side:
(x + -0.3571428572)(x + -0.3571428572) = 28.8418367304

Calculate the square root of the right side: 5.370459639

Break this problem into two subproblems by setting 
(x + -0.3571428572) equal to 5.370459639 and -5.370459639.

Subproblem 1

x + -0.3571428572 = 5.370459639 Simplifying x + -0.3571428572 = 5.370459639 Reorder the terms: -0.3571428572 + x = 5.370459639 Solving -0.3571428572 + x = 5.370459639 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.3571428572' to each side of the equation. -0.3571428572 + 0.3571428572 + x = 5.370459639 + 0.3571428572 Combine like terms: -0.3571428572 + 0.3571428572 = 0.0000000000 0.0000000000 + x = 5.370459639 + 0.3571428572 x = 5.370459639 + 0.3571428572 Combine like terms: 5.370459639 + 0.3571428572 = 5.7276024962 x = 5.7276024962 Simplifying x = 5.7276024962

Subproblem 2

x + -0.3571428572 = -5.370459639 Simplifying x + -0.3571428572 = -5.370459639 Reorder the terms: -0.3571428572 + x = -5.370459639 Solving -0.3571428572 + x = -5.370459639 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.3571428572' to each side of the equation. -0.3571428572 + 0.3571428572 + x = -5.370459639 + 0.3571428572 Combine like terms: -0.3571428572 + 0.3571428572 = 0.0000000000 0.0000000000 + x = -5.370459639 + 0.3571428572 x = -5.370459639 + 0.3571428572 Combine like terms: -5.370459639 + 0.3571428572 = -5.0133167818 x = -5.0133167818 Simplifying x = -5.0133167818

Solution

The solution to the problem is based on the solutions from the subproblems. x = {5.7276024962, -5.0133167818}

See similar equations:

| 2a=-6a-64 | | 2c-8=5c-11 | | 5y^2+30y-35=0 | | C=4x+55 | | 2(10+15)=2(10)+2(15) | | -0.028+20.8= | | 20=14+13(x+8) | | 4x+8=-112-8x | | 8*4=8*4 | | 3t+4=5t-2 | | 2c^2+13c+21=0 | | 2+8=j | | b^2+7b+10=0 | | 3.5I=3 | | 3.6=-1.2h | | 3(3x+2)=14x+4-5x+2 | | 6(5z-1)-5(z+2)=11(z+1) | | 9h=-81 | | 8t+2*t-1= | | X^2+14x-10=0 | | 6x+2*-x-3= | | q(t)=(3t+8) | | 5p-3*2p+4= | | 7r+2*8r= | | y+4*y+3= | | z+7*5z-1= | | (z+7)*(5z-1)= | | 10x-6=6x+14 | | x-5*4=56 | | 6.3=9 | | 3x-9=90 | | 200-3x=33x+24 |

Equations solver categories